Epistemology Abed Al-Jabiri And Its Relevance In The Context Of Islamic Studies In Indonesia - Riady, Ahmad Sugeng (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract This article departs from the fact that Muslims today are experiencing setbacks from various sides. Therefore, philosophers, scientists, and many scholars provide an alternative solution to address such facts, including Abed al-Jabiri. Abed al-Jabiri born, grow, and develop the idea in Morocco. Before plunging into the intellectual world, he was active in the political party with the thought of which tends to be socialist-Marxist. As for the product, the idea can be found in his book entitled Naqdu-l-‘Aqli al-Arabi (Criticism of Reason Arabic) with a thickness of about 1200 pages. Abed al-Jabiri divides the three epistemologies of knowledge of Muslims, namely Bayani that lineup text, offered with a base experience of intuition, and Burhani with a base of reality that is supported with common sense. While the relevance of the third classification is for the study of Islam can be used to map the religious movement in Indonesia. In addition, it can also be used as a departing point to examine the phenomenon of religious diversity through the approach of integrative. Keywords: Islamic, Epistemology, Islamic Studies. Abstrak Artikel ini berangkat dari fakta bahwa umat Islam hari ini mengalami kemunduran dari berbagai sisi. Maka dari itu, para filsuf, ilmuwan, dan ulama banyak memberikan alternatif solusi untuk menjawab fakta tersebut, termasuk Abed al-Jabiri. Abed al-Jabiri lahir, tumbuh, dan mengembangkan gagasannya di Maroko. Sebelum terjun ke dunia intelektual, ia sempat berkiprah di partai politik dengan pemikiran yang cenderung sosialis-marxis. Adapun produk gagasannya dapat ditemukan di bukunya yang berjudul Naqdu-l-‘Aqli al-Arabi (Kritik Nalar Arab) dengan tebal sekitar 1200-an halaman. Abed al-Jabiri membagi tiga epistemologi pengetahuan umat Islam, yakni bayani yang berbabis teks, irfani dengan basis pengalaman intuisi, dan burhani dengan basis realitas yang didukung dengan akal. Sedangkan relevansi dari ketiga klasifikasi tersebut untuk studi Islam dapat digunakan untuk memetakan gerakan keagamaan yang ada di Indonesia. Selain itu juga dapat digunakan sebagai titik berangkat untuk mengkaji fenomena keagamaan yang beragam melalui pendekatan yang integratif. Kata Kunci : Islam, Epistemologi, Studi Islam.